(3GOGQI GdehGQO GdHTQjI (B/s - (3cGed, eUWai eUWais ((3GdbGgQI(B: s (3GdTQcI GdYQHjI ddfTQ hGdJhRjY(B, s, 1994)
(3aj gPG GdcJGH (B: (3eONd eaGgej (B. (3GdJMdjd GdJfXjej , GdSdhc GdJfXjej YdGbGJ GdYed (B:(3GdUQGY hGdJZjjQ , GOGQI GdCaQGO GdYdGbGJ GdUfGYjIs
Keywords: (3GOGQIs; (3GdCaQGOs; (3ehGQO HTQjIs